Kompetensi Guru Profesional: Potret Perjuangan Pendidikan Islam Syekh Jalaludin - Mirzon Daheri; Edi Nurhidin; Idi Warsah (Rumah Jurnal Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2022)
Teacher professionalism requires the fulfillment of the four types of competencies that are manifested in competency tests and teacher certification. Apart from these two things, there are other ways that teachers can do it independently, namely learning from local history. Understanding of local history has many benefits. In this context, that understanding can be a source of motivation and inspiration to become a professional teacher. Therefore, this study seeks to reveal the dimensions of teacher competence in local history context, namely about Sheikh Jalaludin's struggle for Islamic education. The research type used in this research was field research using a qualitative descriptive approach. Data collection was carried out by interviewing the head of the Customary Consultative Agency (BMA-Badan Musyawarah Adat), community leaders, and religious leaders. The data was analyzed using an interactive analysis model which consisted of three stages, including: data condensation, data presentation, and drawing conclusions. The study results prove two things. First, Sheikh Jalaludin's Islamic education strategy uses a gradual Sufistic approach, namely by adapting to the environment and the customs of the community to gain their empathy. Second, its success in Islamizing society reflects the professional and ideal dimensions of teacher competence. This study concludes that local historical experience is an important aspect that can inspire teachers to improve their competence and ideals as professional educators.